The use of differential pulse voltammetries to discriminate between the Butler-Volmer and the simple Marcus-Hush models for heterogeneous electron transfer: The electro-reduction of europium (III) in aqueous solution - Wang, Y; Laborda, E; Henstridge, M; Martinez-Ortiz, F; Molina, A; Compton, R (2012)
Differential multipulse voltammetry and square wave voltammetry are employed to critically compare and discriminate between the Butler-Volmer and Marcus-Hush kinetic formalisms of heterogeneous electron transfer. The reduction of europium (III) in aqueous solution is studied with mercury hemispherical microelectrodes. By using these differential pulse techniques in reverse scan mode, both the reduction and oxidation half-reactions can be evaluated at the same time and are very appropriate for kinetic analysis due to the reduction of charging current and background effects and the sensitivity of the peak height to the electrode kinetics. Numerical simulations using both theories are employed to fit the experimental voltammograms. The results show that the Butler-Volmer model parameterizes satisfactorily all the experimental data. Consistent values of the standard heterogeneous rate constant and the transfer coefficient are obtained with different techniques and different conditions of pulse times and frequency. In contrast, the Marcus-Hush model in its simple form does not yield a satisfactory description of the voltammograms of this redox couple in any case, which demands a critical revision of the kinetic approach. © 2012 Elsevier B.V. All rights reserved.